2003
DOI: 10.1007/bf02504553
|View full text |Cite
|
Sign up to set email alerts
|

A tool for helping veterinary students learn diagnostic problem solving

Abstract: This study describes the result of implementing the Problem List Generator (PLG), a computer-based tool designed to helpYou aren't feeling well, so you go to your doctor. A physical exam reveals nothing obvious, so blood and urine samples are sent to the lab. When the results come back, your doctor has a problem. The extent to which that problem is resolved satisfactorily (and, perhaps, your health) depends on your doctor's ability to interpret all the data that have been collected. This skill, the process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…This is in line with the research conducted by Danielson, et al (2003) stating that, by problem based learning strategy, the ability of students' problem solving can increase because the students are habitually faced with learning problems and their solutions. Further, in their research, Sungur and Tekkaya (2006) stated that the class applying problem-based learning has high intrinsic motivation, influences meaning in doing the job, increases the ability to think critically and creatively, has metacognitive and self regulated learning, if compared with the class applying conventional learning.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with the research conducted by Danielson, et al (2003) stating that, by problem based learning strategy, the ability of students' problem solving can increase because the students are habitually faced with learning problems and their solutions. Further, in their research, Sungur and Tekkaya (2006) stated that the class applying problem-based learning has high intrinsic motivation, influences meaning in doing the job, increases the ability to think critically and creatively, has metacognitive and self regulated learning, if compared with the class applying conventional learning.…”
Section: Discussionsupporting
confidence: 87%
“…The full questionnaire used in the study is found elsewhere (Danielson et al, 2003), and was designed to determine the students' perceptions of the dP's clarity (or usability), feasibility, and learning impact. We will focus on the items having to do with learning impact --items 6, 7, 12, 16, and 17 (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, unlike the tools described by Jonassen (2003) in that it imposes more structure upon the way students approach problems. The dP has been described in detail elsewhere (Danielson, 1999;Danielson, Bender, Mills, Vermeer, & Lockee, 2003), though a brief description follows. The dP presents veterinary cases, and allows learners to explain the data for a given case; it involves four core learning interactions: 1. collect historical data, 2. collect laboratory data, 3. synthesize data into a solution called a diagnostic path, and 4. compare the learner solution to an expert solution.…”
Section: The Diagnostic Pathfindermentioning
confidence: 99%
See 2 more Smart Citations